Construction and Verification of a Glycolysis-Associated Gene Signature for the Prediction of Overall Survival in Low Grade Glioma - Liu, Wei; Liu, Chunshan; Chen, Chengcong; Huang, Xiaoting; Yi, Qi; Tian, Yunhong; Peng, Biao; Yuan, Yawei (Frontiers in Genetics, 2022)
The overall survival of patients with lower grade glioma (LGG) that might develop into high-grade malignant glioma shows marked heterogeneity. The currently used clinical evaluation index is not sufficient to predict precise prognostic outcomes accurately. To optimize survival risk stratification and the personalized management of patients with LGG, there is an urgent need to develop an accurate risk prediction model. The TCGA-LGG dataset, downloaded from The Cancer Genome Atlas (TCGA) portal, was used as a training cohort, and the Chinese Glioma Genome Atlas (CGGA) dataset and Rembrandt dataset were used as validation cohorts. The levels of various cancer hallmarks were quantified, which identified glycolysis as the primary overall survival related risk factor in LGGs. Furthermore, using various bioinformatic and statistical methods, we developed a strong glycolysis related gene signature to predict prognosis. Gene set enrichment analysis showed that in our model, high-risk glioma correlated with the chemoradiotherapy resistance and poor survival. Moreover, based on established risk model and other clinical features, a decision tree and a nomogram were built, which could serve as useful tools in the diagnosis and treatment of LGG. This study indicates that the glycolysis-related gene signature could distinguish high risk and low‐risk patients precisely, and thus can be used as an independent clinical feature.